الاتجاهات الحديثة لأزمة الغذاء العالمية وطرق مواجهتها: Recent trends in the global food crisis and ways to confront it - ياسر محمود احمد عبدالرحمن; مصطفى احمد محمود عبدالمجيد (Journal of North African Economies, 2025)
The food problem is one of the problems facing humanity, and perhaps the most acute in our current era, as it directly affects the lives and survival of hundreds of millions of people, as it sweeps all countries of the world, especially third world countries, where individuals spend a very large percentage of their income on food, especially after the increase in grain prices, as prices increased significantly in 2021, due to events that harm food commodities such as climate change, natural disasters and global epidemics such as the Corona pandemic, which greatly affected the supply of global food commodities due to the closure of many factories and ports, and then came the Russian-Ukrainian war in 2022, which led to prices reaching their highest levels as a result of the disruption of the flow of primary commodities from two of the world's largest countries exporting wheat and other basic consumer goods. Within the framework of the above, we will present the most important modern trends in the global food crisis by focusing on the Corona pandemic, the Russian-Ukrainian war and the demand for biofuels in the first section entitled Review of Previous Studies That Addressed the Global Food Crisis, then the second section entitled Theoretical Framework of the Study and the third section Modern trends towards confronting the global food crisis at the international and local levels